The reaction of N-isocyaniminotriphenylphosphorane (NICITPP) with 2-oxopropyl-1-benzenecarbothioate and a primary amine in the presence of benzoic acid derivatives. (1st February 2016) - Ramazani, Ali; Nasrabadi, Fatemeh Zeinali; Ahankar, Hamideh; Asiabi, Pegah Azimzadeh; Sadri, Fariba; Joo, Sang Woo
GRAPHICAL ABSTRACT: ABSTRACT: Reactions of N-isocyaniminotriphenylphosphorane (NICITPP) with 2-oxopropyl-1-benzenecarbothioate in the presence of aromatic carboxylic acids and primary amines proceed smoothly at room temperature (18–26°C) and in neutral conditions to afford sterically congested 1, 3, 4-oxadiazole derivatives in high yields. The reaction progresses smoothly and clearly under mild conditions and no side reactions were observed.